Model choice and decision theory - Rossi, Peter (Henry Stewart Talks, 2010)
Model selection, Bayes factors, Asymptotic methods, Newton raftery, Marketing decisions and BDT, Lost and profit functions, Why full Bayes?, Value of disaggregate information, Value of household purchase information, Couponing example